Opakovaná lokální trombolýza u poranení a trombózy axilární a podklíckové zíly - Sárník, S; Hofírek, I (Vnitrni lekarstvi, 2009)
Deep vein thrombosis (DVT) is a disorder with blood clot (thrombus) formation in deep veins. DVT of upper extremities (UE) is rare but serious, bearing in mind its possible complications, disease. UE DVT treatment involves subcutaneous injections of low molecular weight heparins and subsequent switch to oral anticoagulation or thrombolysis; thrombolysis by intravenous administration of a thrombolytic agent is used only if indicated (subclavian vein thrombosis). A case of a professional sportswoman is presented, who was treated for venous thrombosis of subclavian and axillary veins using local thrombolysis. Thrombosis emerged suddenly after a basketball match, during which oedema of the right arm occurred subsequent to the patient being hit with the ball to the armpit area. Venipuncture as well as all catheter repositionings were performed under the duplex ultrasound (DUS) surveillance. Proximal brachial vein was punctured and four French catheters were used to enter subclavian vein. For thrombolysis, 0.2-0.6 mg/hour alteplase (rt-PA) was used. Injury to axillary vein tunica intima was evident the following day after the subclavian and axillary thrombosis was dissolved completely, and thrombosis in the same area recurred immediately after stopping the thrombolytic infusion. Therefore, administration of a thrombolytic agent into the same area was re-introduced and acetylsalicylic acid was added to the medication. This combined therapy resulted in recanalization of the arm as well as the axillary and subclavian areas. Thrombolysis was stopped on the 3rd day of treatment. The method can be used to manage deep vein thromboses of the upper arms even without X-ray control. Local thrombolysis of deep vein thrombosis with ultrasound surveillance is, in indicated patients, a safe method even if a vein injury occurs.
Keywords: intervenční ultrasonografie; Humans; Thrombolytic Therapy; trombolytická terapie; žilní trombóza; mladý dospělý; poranění paže; Female; Venous Thrombosis; lidé; Tissue Plasminogen Activator; Retreatment; Ultrasonography, Interventional; fibrinolytika; Fibrinolytic Agents; vena axillaris; ženské pohlaví; basketbal; vena subclavia; tkáňový aktivátor plazminogenu; Arm Injuries; Aspirin; Young Adult; Basketball; Axillary Vein; Subclavian Vein; opakovaná terapie